Ferroptosis and cuproptosis in periodontitis: recent biological insights and therapeutic advances - Zheng, Tengyi; Lu, Fumiao; Wu, Peihang; Chen, Yangan; Zhang, Rongxin; Li, Xin (Frontiers in Immunology, 2025)
Periodontitis is a significant global public health issue associated with the onset and progression of various systemic diseases, thereby requiring additional research and clinical attention. Although ferroptosis and cuproptosis have emerged as significant areas of research in the medical field, their precise roles in the pathogenesis of periodontitis remain unclear. We aim to systematically summarize the current research on ferroptosis and cuproptosis in periodontal disease and investigate the roles of glutathione pathway and autophagy pathway in connecting ferroptosis and cuproptosis during periodontitis. Further, we propose that a homeostatic imbalance of copper and iron, driven by periodontal pathogens, may contribute to elevated periodontal oxidative stress, representing a potential unifying link between ferroptosis and cuproptosis involved in periodontitis. This article presents a comprehensive overview of the molecular mechanisms underlying ferroptosis and cuproptosis in periodontitis, offering novel theoretical insights into its pathogenesis and potential therapeutic targets.